Catalytic hydrolysis of sodium borohydride solution for hydrogen production using thermal plasma synthesized nickel nanoparticles. (24th June 2020) - Ghodke, N.P.; Rayaprol, S.; Bhoraskar, S.V.; Mathe, V.L.
Abstract: In the present study nickel nanoparticles were synthesized by thermal plasma route. In this method we obtained highly crystalline almost spherical nanoparticles with maximum number of particles having size around 30–50 nm. These nanoparticles were thoroughly characterized and employed as a catalyst for hydrogen production using hydrolysis of sodium borohydride (NaBH4 ). The effect of initial concentration of NaBH4, pH and temperature of solution on the rate of hydrogen production was investigated. Nickel nanoparticles exhibits first order reaction with respect to NaBH4 concentration at elevated temperatures. After hydrolysis, the nickel nanoparticles showed presences of B–O and B–OH species on the nickel surface. The catalyst was found to be stable during 5 sequential cycles of test. Graphical abstract: Image 1 Highlights: Synthesis of highly crystalline nickel nanoparticles by thermal plasma route. Maximum rate of hydrogen production was 1000 ml/min/gcatalyst at 320 K for 0.661 M NaBH4 solution having 9 pH. Reaction kinetics followed during hydrogen production under different experimental conditions has investigated. Post characterization of catalyst depicts presence of B–O and B–OH functional groups at the surface of Ni catalyst.